Habit, Symmetry and Orientation of Surface Structures Vapor - Phase Condensation SnTe:Bi on Ceramics - Saliy, Ya.P.; Makovyshyn, V.I.; Bylina, I.S.; Bushkov, N.I. (Physics and Chemistry of Solid State, 2016)
The analysis was obtained by atomic force microscopy method of topograms nanostructures on the surface of vapor-phase condensation of SnTe: Bi, thet were opened deposited by evaporation in a vacuum on substrates of ceramics. With the distribution of polar and azimuthal angles of the normal vector to the surface elements of condensate was found objects with flat faces with by dominant orientation in space and by symmetry.